Highly Conductive Amorphous Pentlandite Anchored with Ultrafine Platinum Nanoparticles for Efficient pH‐Universal Hydrogen Evolution Reaction. (6th August 2021) - Zhang, Chenxu; Cui, Yanan; Yang, Yilin; Lu, Linguo; Yu, Shansheng; Meng, Zeshuo; Wu, Yixian; Li, Yaxin; Wang, Yanan; Tian, Hongwei; Zheng, Weitao
Abstract: The devise and fabrication of highly efficient electrocatalysts have momentous practical significance for the development of future hydrogen energy systems. However, their potential uses in support construction are not well studied. In this work, a highly efficient electrocatalyst is developed for the hydrogen evolution reaction by anchoring single Pt atoms and clusters into functional amorphous pentlandite Fe5 Ni4 S8 (or FNS) to yield Pt–FNS composites. Amorphous FNS still provides great conductivity to the composites, thereby promoting rapid charge transfer. The presence of abundant defects in Pt–FNS composite catalysts induces pleasant atomic dispersion and anchoring of Pt species. In addition, the formation of single Pt atoms combined with clusters and low‐Pt‐loading improves the utilization of Pt and reduces the cost. The turnover frequency analysis suggests Pt–FNS systems possess significant unit catalytic activity. The synergetic catalytic effect issued from high conductivity, abundant active sites and elevated intrinsic activity forms Pt–FNS systems with efficient pH‐universal catalytic activity. The systems exhibit low overpotentials of only 30, 65, and 98 mV at 10 mA cm −2 under acidic, alkaline, and neutral conditions, respectively. In sum, the proposed route looks promising for the fabrication of new electrocatalysts with improved properties. Abstract : Amorphous Fe5 Ni4 S8 as a carrier realizes anchoring and dispersion of Pt nanoparticles in Pt/Fe5 Ni4 S8 composite with low content and atomic level while maintaining high conductivity. The presence of large amounts of S atoms is beneficial to the adsorption of hydrogen protons and water molecules, leading to composites with excellent pH‐universal hydrogen evolution reaction performance.